2011
DOI: 10.1007/s12070-011-0278-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Endoscopic Sinus Surgery in Patients with Symptomatic Chronic Rhinosinusitis with Minimal Changes on Computerised Tomography

Abstract: This study was designed to assess the efficacy of functional endoscopic sinus surgery (FESS) in chronic rhinosinusitis (CRS) patients with minimal radiological findings, and based on one centre, prospective randomized controlled study, conducted in the Department of Otorhinolaryngology, Lady Hardinge Medical College, New Delhi. All the CRS out-patients ([18 years) refractory to 3 weeks of medical therapy were radiologically evaluated with computerised tomographic scan (CT) of nose and paranasal sinuses. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Our findings were comparable to Chakravarti et al who reported nasal obstruction and nasal discharge are the two most common symptoms, 94% and 91%, respectively, with headache occurring in 63% of patients. 16 Conversely, Bohman et al reported a slightly different picture in their study, with disturbance in olfaction being the most common symptoms at a frequency of 76.6% and nasal obstruction occurring in only 55.3% of cases. 17 Our study compared the utility of employing FESS hybrid therapy (in combination with a short course of drug therapy) with purely conservative management as first-line therapy for patients with nasal polyps secondary to chronic rhinosinusitis and found it to be an effective measure in this role, both in improving symptoms as well as in improvements in the Lund-MacKay CT scores.…”
Section: Discussionmentioning
confidence: 77%
“…Our findings were comparable to Chakravarti et al who reported nasal obstruction and nasal discharge are the two most common symptoms, 94% and 91%, respectively, with headache occurring in 63% of patients. 16 Conversely, Bohman et al reported a slightly different picture in their study, with disturbance in olfaction being the most common symptoms at a frequency of 76.6% and nasal obstruction occurring in only 55.3% of cases. 17 Our study compared the utility of employing FESS hybrid therapy (in combination with a short course of drug therapy) with purely conservative management as first-line therapy for patients with nasal polyps secondary to chronic rhinosinusitis and found it to be an effective measure in this role, both in improving symptoms as well as in improvements in the Lund-MacKay CT scores.…”
Section: Discussionmentioning
confidence: 77%
“…Two publications are worth being mentioned – one is retrospective, randomized, and controlled – where patients with symptoms of CRS after drug therapy and only low-grade findings in the CT scan (Lund-Mackay score of 0–6) stated an improvement in around 80% one year after endoscopic sinus surgery, comparable to the one of patients with more important symptoms (Lund-Mackay score of 7–24; [ 1225 ], [ 1226 ].…”
Section: Results (Outcome)mentioning
confidence: 99%
“…Although the evidence has been conflicting, 28,29 some studies have shown that greater radiographic CRS disease severity may be associated with better outcomes after ESS 30‐32 and one retrospective study has suggested that symptoms/revision ESS rate may not be improved by ESS beyond affected sinuses 33 . In comparison, other studies have shown patients with minimal radiographic evidence of sinus disease but who have medically recalcitrant symptoms of suspected sinonasal origin can experience significant improvement in QOL from ESS 34‐37 . Finally, it should be noted that all these studies have focused on global radiographic CRS disease severity and none have made any inferences on a sinus‐by‐sinus basis.…”
Section: Discussionmentioning
confidence: 99%
“…33 In comparison, other studies have shown patients with minimal radiographic evidence of sinus disease but who have medically recalcitrant symptoms of suspected sinonasal origin can experience significant improvement in QOL from ESS. [34][35][36][37] Finally, it should be noted that all these studies have focused on global radiographic CRS disease severity and none have made any inferences on a sinus-by-sinus basis. The degree to which global radiographic CRS burden is independently predictive of ESS outcomes therefore remains unclear-and there is no evidence reporting ESS outcomes on a sinus-by-sinus basis-although the presence of symptoms suspected to be sinonasal etiology may be an important determinant in the relationship between radiographic disease burden and ESS outcomes.…”
Section: Discussionmentioning
confidence: 99%